Efficacy of VG26 and K1 acupuncture points in cardiopulmonary resuscitation of neonatal puppies born by cesarean section - Lourenço, Maria Lucia G.; Knupp, Fabíola C.; Pereira, Keylla Helena N. P.; Fuchs, Kárita M.; Xavier, Gleice M.; Mendonça, Júlia C.; Tsunemi, Miriam Harumi; Souza, Fabiana F.; Joaquim, Jean G. F. (Frontiers in Veterinary Science, 2025)
The aim of this study was to evaluate the effects of acupuncture points VG26 and K1 on the reversal of apnea and the elevation of heart and respiratory rates in neonatal dogs after birth. Sixty neonates who were apneic, bradycardic, bradypneic or dyspneic were divided into three groups: VG26 acupuncture point (GVG26), K1 acupuncture point (GK1), and control (CG). Data on heart rate (HR), respiratory rate (RR) and Apgar score were collected. The moments of analysis were after 1 min of tactile respiratory stimulus (M1); after stimulation with the acupuncture points (M2); and 10 min after the last assessment (M3). After the VG26 and K1 were used, a significant increase in HR was observed between M1 and M2, medians (25% quartile–75% quartile), respectively: GVG26 136 and 202 bpm; GK1 147 and 195 bpm; GC 168 and 187 bpm. Significant clinical improvement was also observed in RR, with a median at M1 and M2, respectively: GVG26 16 and 28 mpm; GK1 18 and 32 mpm; GC 32 and 40 mpm. For the Apgar score, significant differences were observed in the mean scores between M1 and M3 in the GVG26, GK1 and CG groups. The VG26 and K1 acupuncture points are effective in neonatal puppies, leading to improvements in the respiratory pattern and increases in the HR, RR and Apgar score, can be used in neonatal resuscitation at birth.